De novo synthesis of astaxanthin: From organisms to genes. (October 2019) - Fang, Ning; Wang, Chunkai; Liu, Xiaofeng; Zhao, Xue; Liu, Yanhua; Liu, Xinmin; Du, Yongmei; Zhang, Zhongfeng; Zhang, Hongbo
Abstract: Background: Astaxanthin is a ketocarotenoid with stronger antioxidant activity than vitamin E and coenzyme Q10, and with pharmacological effects against cancer, cardiovascular disease, diabetes, inflammation, and others. Increased astaxanthin supplementation in foods, nutraceuticals, and cosmetic products has resulted in tremendous growth in the demand for natural astaxanthin. Scope and approach: Astaxanthin is found widely in aquatic animals and some other organisms, but its de novo synthesis is limited to several bacteria, protists, fungi, algae and plants. Metabolic engineering offers approaches to create systems for high-efficiency production of astaxanthin, which will require in-depth dissection of the astaxanthin synthesis enzymes in the available organisms. Key findings and conclusions: Here, we review the de novo synthesis of astaxanthin in bacteria, protists, fungi, algae and plants, and the functional enzymes of specific organisms. A protein-sequence based phylogenetic tree was established to reveal the evolutionary relationships of astaxanthin synthesis proteins across organisms. This review will provide valuable information for the metabolic engineering of astaxanthin bioreactors. Highlights: Astaxanthin is a strong antioxidant with multiple pharmacological effects. Astaxanthin supplementation in health products is in tremendous increase. Engineering of astaxanthin production requires dissection of the synthetic enzymes. De novo synthesis of astaxanthin in bacteria, protists, fungi, algae and plants is summarized. Phylogenetic tree of astaxanthin synthetic enzymes is established.